2011
DOI: 10.1016/j.actatropica.2010.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exposure to Euphorbia splendens var. hislopii latex on the concentrations of total proteins and nitrogen products in Biomphalaria glabrata infected with Schistosoma mansoni

Abstract: The aim of this work was to analyze the content of total protein and nitrogen degradation products in Biomphalaria glabrata infected with Schistosoma mansoni and exposed to Euphorbia splendens var. hislopii latex. The LC(50) of this latex was 1.0mg/l. Concentrations of uric acid, urea and total proteins were determined in the hemolymph of B. glabrata infected with five S. mansoni miracidia and exposed to a sublethal concentration of E. splendens var. hislopii latex for 24h. The exposure to this molluscicide ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…This phenomenon leads to mobilization of the energy reserves in the tissues to the haemolymph, promoting glucose homeostasis (Bezerra et al, 1999). Similar physiological alterations are observed in snails submitted to other physiological stresses such as severe starvation, aestivation (Becker, 1980), exposure to natural molluscicides (Mello-Silva et al, 2010) and association of infection with molluscicides (Mello-Silva et al, 2011).…”
Section: Resultsmentioning
confidence: 81%
“…This phenomenon leads to mobilization of the energy reserves in the tissues to the haemolymph, promoting glucose homeostasis (Bezerra et al, 1999). Similar physiological alterations are observed in snails submitted to other physiological stresses such as severe starvation, aestivation (Becker, 1980), exposure to natural molluscicides (Mello-Silva et al, 2010) and association of infection with molluscicides (Mello-Silva et al, 2011).…”
Section: Resultsmentioning
confidence: 81%
“…Other studies have shown that the application of substances derived from E. milii in water bodies in transmission areas leads to changes in physiological stocks and S. mansoni/B. glabrata compatibility [16][17][18]. The effects of E. milii latex on the parasite life cycle in both schistosomiasis hosts (snails and mammals) have been described.…”
Section: Introductionmentioning
confidence: 99%
“…It is active against mollusks which are intermediate hosts of Schistosomatrematodes at concentrations as low as 0.5 ppm in the laboratory and at concentrations as low as 5.0 ppm under field conditions (Vasconcellos&Schall, 1986;Mendes et al, 1992). Besides its remarkable potency, E. milii latex also presents other advantages as a molluscicide: E. milii can be easily cultivated in endemic areas and yields a rather large amount of latex throughout the year, no marked seasonal nor geographic variation have been found in the molluscicidal activity, and the latex has proved to be less harmful to nontarget organisms than niclosamide, today's mostly used synthetic molluscicide (Baptista et al, 1994;Oliveira-Filho et al, 2000;Yadav &Jagannadham, 2008;Oliveira-Filho et al, 2010;Mello-Silva et al, 2011).…”
Section: _164mentioning
confidence: 99%